1996
DOI: 10.1128/jcm.34.12.3007-3011.1996
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of community-acquired viral infections due to respiratory viruses in Rhone-Alpes (France) during winter 1994 to 1995

Abstract: Nasal swab samples from patients with acute flu-like illness were evaluated for the presence of respiratory viruses in the Rhone-Alpes region of France from 1 October 1994 through 2 May 1995. The relative frequencies and seasonal distributions of the specific viruses were assessed. In addition, virus type was correlated with specific clinical signs and symptoms. During the study, 962 samples were collected by 75 medical practitioners participating in the Groupe Regional d'Observation de la Grippe surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
54
3
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 24 publications
17
54
3
5
Order By: Relevance
“…HCoV-229E and OC43 are widespread and responsible for one-third of common colds in children and adults [6]. They have been detected in nasal swab samples from patients with acute flu-like illness [19] and also in human brain autopsy samples [18]. It has been suggested they may also be involved in the etiology of more severe diseases in all age groups (pneumonia, perimyocarditis, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…HCoV-229E and OC43 are widespread and responsible for one-third of common colds in children and adults [6]. They have been detected in nasal swab samples from patients with acute flu-like illness [19] and also in human brain autopsy samples [18]. It has been suggested they may also be involved in the etiology of more severe diseases in all age groups (pneumonia, perimyocarditis, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…RSV was the most common agent (36%), followed by HCoV (18.4%). 23 Children hospitalized during the epidemic period often introduce respiratory viruses into the hospital. 7 Goldwater et al reported a rate of 47% in asymptomatic children hospitalized in a paediatric unit, higher than our 23.2%.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that human coronavirus infections are not very common cause of respiratory infections in young children [38], whereas later in life, clinical and subclinical infections occur more often [39]. Adenoviruses infrequently cause common colds, and respiratory infections caused by these viruses tend to be severe, characterized by high and prolonged fever and strong inflammatory response [40,41]. Adenoviruses more often cause occasional epidemics in semiclosed communities, such as garrisons or orphanages [42].…”
Section: Specific Features Of Respiratory Virusesmentioning
confidence: 99%